Evaluation of commercially available herbicides for weed control in cassava - Moyo, C.C.; Jumbo, S.; Mahungu, N.M.; Benesi, I.R.M.; Ntawuruhunga, Pheneas; Sandifolo, V.S. (International Association of Hydrological Sciences, 2012)
A trial was conducted in 2008/09 at Chitedze (31o 59' S; 33o 38' E) and Chitala (13o 40' S; 34o 15' E) Research stations in Malawi to evaluate commercially available pre-emergent herbicides for weed control in cassava (Manihot esculenta Crantz). Four herbicides, Bullet (chloroacetanilide, dimethanamid, triazine), Harness 90 EC (chloroacetanilide), Codal Gold 412-5 EC (prometryn and S-metolachlor) and Metalachlor 960 EC (S-metolachlor; acetamide), were evaluated with and without follow up hand-hoe weeding (check). Panicum maximum, Elusine indica, Rottboellia chochinchinensis and Setaria pumila were the common narrow-leaved weeds while Commelina benghalensis, Bidens pilosa, Nicandra physalodes and Acanthospermum hispidum were the common broad leaved weeds. Herbicide application did not affect crop establishment but significantly (P<0.001) reduced early weed growth by 74.8 to 91.2 % at Chitedze and 53.7 to 97.9 % at Chitala. Bullet was more effective in early weed control (2.8 weeds m-2 at Chitedze and 0.0 weeds m-2 at Chitala) than the other herbicides (38.7 weeds m-2 at Chitedze and 8.8 weeds m-2 at Chitala) and resulted in root yields (12.3 t ha-1 at Chitedze and 18.4 t ha-1 at Chitala) and returns (MK238,844.00 ha-1 at Chitedze and MK360,779.00 ha-1 at Chitala) comparable to or higher than hand weeding (root yield of 10.6 t ha-1 at Chitedze and 16.3 t ha-1 at Chitala and returns of MK2 0 1 , 4 3 8 . 0 0 h a - 1 a t Ch i t e d z e a n d MK310,448.00 ha-1 at Chitala) and other treatments (root yield of 2.2-13.1 t ha-1 at Chitedze and 1.3-23.6 t ha-1 at Chitala and returns of MK44,000.00 to MK249,078 at Chitedze and MK26,000.00 to MK465,100 ha-1 at Chitala), making it a potential alternative to hand hoe weeding in cassava.